PERBANDINGAN HASIL BELAJAR MODEL PEMBELAJARAN ARIAS DENGAN INKUIRI ILMIAH TEKNIK PICTORIAL RIDDLE - Pramita Sylvia Dewi; Agus Suyatna; Nengah Maharta (Jurnal Pembelajaran Fisika, 2013)
Student learning outcomes can be improved applying a learning model ARIAS and Scientific Inquiry Pictorial Techniques Riddle. This study aims to: (1) know the difference between average yield learnng physics students taught using inquiry learning model ARIAS with Scientific Techniques Pictorial Riddle, (2) determine average physics student learning outcomes are higher among ARIAS learning model with Scientific inquiry Pictorial Techniques Riddle. This research has been carried out in second semester of school year 2012/2013 in SMAN 13 Bandarlampung and the sample class XI IPA2 and XI IPA1 totaling 80 students. The sampling technique used cluster random sampling. The design is One-Shot Case Study. Learning outcomes data obtained from average achievement test. Data were analyzed using independent sample t test. The results of analysis of data with an average value of learning outcomes in the classroom ARIAS at 64.39 while Pictorial Technique of Scientific Inquiry class Riddle of 74.91. Thus be concluded: (1) There is difference between average yield learning physics students taught using inquiry learning model ARIAS with Scientific Techniques Pictorial Riddle, (2) Average yield learning physics students taught using learning model ARIAS lower than average learning outcomes of students who were taught physics model Pictorial Riddle Engineering Scientific Inquiry.Key words: ARIAS, Scientific Inquiry Pictorial Techniques Riddle, and learning outcomes.